Royal's bride - Martin, Kat. (Don Mills, Ont. : MIRA, 2009)
Royal has returned to Bransford Castle to find his father dying and the family treasury nearly empty. The duke wrests a final promise from his son: that Royal will marry heiress Jocelyn Caulfield and restore the estate. However, it is not his fiancě who quickens Royal's pulse, but rather her beautiful cousin Lily Moran.
Keywords: Arranged marriage -- Fiction; Man-woman relationships -- Fiction; Great Britain -- History -- Fiction; Historical fiction; Love stories